Hypertension Among Dental Patients: A Single Institution Experience And Development Of A Working Clinical Algorithm For Dental Practitioners - Nalisha Mohamed Ramli; Raid Hamizan Mohd Zulkifle; Aqilah Salmi Abdul Salam; Nor Azura Ahmad Tarmidzi; Norashikin Amran (UM Press, 2026)
Indexed by MYCITE